1837-38 Tenn. Pub. Acts 200-01, An Act to Suppress the Sale and Use of Bowie Knives and Arkansas Tooth Picks in this State, ch. 137, § 2 - (:unkn) unknown (My University, 1837)
Prohibited the carrying of a concealed Bowie knife, Arkansas tooth pick, or other knife or weapon. Punishable by fine of $200-500 and imprisonment for 3-6 months.
Keywords: CARRY - CONCEALED - NON-GUN ARMS